Entrepreneurial Strategies for Surviving Economic Uncertainty: A Reflection on the Sustainability of MSMEs in Indonesia: Strategi Wirausaha Bertahan di Tengah Ketidakpastian Ekonomi: Refleksi Keberlangsungan UMKM di Indonesia - nurjaya, Nurjaya (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2025)
This study analyzes entrepreneurial strategies for sustaining MSMEs amid Indonesia’s economic uncertainty. Challenges such as market fluctuations, limited capital, and rising operational costs have significantly impacted MSME performance. Using a descriptive qualitative approach through literature review, the study identifies product diversification, digitalization, and cash flow management as key adaptive strategies. Digitalization improves competitiveness and operational efficiency, while financial literacy and daily cash tracking strengthen business resilience. The study also highlights the critical role of government support and cross-sector collaboration in building a sustainable MSME ecosystem. The findings provide strategic insights for MSMEs and policymakers to formulate adaptive responses and long-term resilience strategies in the face of economic volatility.